PEMELIHARAAN JALAN KOTA WANGGUDU KABUPATEN KONAWE UTARA - Darwin Darwin; Muh. Syarif; Edward Ngii (Universitas Halu Oleo, 2020)
Policy in financing the maintenance of Wanggudu City Road North Konawe Regency 2018 with the intention to obtain information objectively in the implementation of the Wanggudu City Road Maintenance Policy in North Konawe Regency implementation period 2014 -2018. This study aims to identify road segments, and determine priorities for road maintenance and analyze road financing and maintenance policies in Wanggudu Raya City. There are 15 city roads that were sampled in the study. Data obtained from observations (observations) directly, then other data in the form of Regional Spatial Detail Plan Data Data obtained from observations (observation) directly, then other data in the form o f Spatial Detail Plan for North Konawe Regency and budgeting and policies contai ned in local regulation. The object of the research is the 15 Wanggudu city road sections, North Konawe Regency roads and the budgeting and policies contained in the regional regulations. The object of research is Wanggudu city road sections, amounting to 15 road sections. The results showed that of the 15 roads there were routine maintenance given to 6 roads with a total length of 24,38 km. Then periodic maintenance is given to 6 roads with a total length of 7 km, and improvements are given to 2 roads with a total length of 1.5 km and reconstruction is given to only 1 road with a total length of 5,82 km. Then from the allocation of funds based on the ability of the region shows that the realization of financing for routine maintenance, periodic maintenance, improvement and reconstruction can only be achieved by 75.95%. Keywords: Po licy, Financing, Maintenance